2002
DOI: 10.1080/09638280110066794
|View full text |Cite
|
Sign up to set email alerts
|

Toward a comprehensive evaluation of the impact of electronic aids to daily living: evaluation of consumer satisfaction

Abstract: Combining the QUEST with outcome measurement tools that explore other important dimensions such as the effect on quality of life and psychosocial impact will help service providers to justify the costs associated with the prescription of sophisticated, costly assistive devices such as EADLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 21 publications
(16 reference statements)
1
19
0
Order By: Relevance
“…The QUEST ascertains a person's positive or negative valuation of assistive device dimensions, as influenced by expectations, perceptions, attitudes and personal standards (Stickel, Ryan, Rigby, & Jutai, 2002). The psychometric properties of the QUEST 2.0 have been verified for individuals with disabilities and can be used for both adults and adolescents (Demers, Ska, Girous, & Weiss-Lambrou, 1999;Demers et al, 2002).…”
Section: Questmentioning
confidence: 99%
“…The QUEST ascertains a person's positive or negative valuation of assistive device dimensions, as influenced by expectations, perceptions, attitudes and personal standards (Stickel, Ryan, Rigby, & Jutai, 2002). The psychometric properties of the QUEST 2.0 have been verified for individuals with disabilities and can be used for both adults and adolescents (Demers, Ska, Girous, & Weiss-Lambrou, 1999;Demers et al, 2002).…”
Section: Questmentioning
confidence: 99%
“…This is an aspect of decreased burden of care which we have included within the . No study to date has found clear evidence of cost savings or potential savings suggesting a need for further investigation 7,41 . However Ripat & Strock (2004) suggested that the main benefit of EADLs may not be financial but may relate more to improved subjective quality of life for users 21 .…”
Section: Time Alonementioning
confidence: 99%
“…EADL can reduce overall worry by providing an element of safety for both parties in the caregiving relationship. Safety and security is well documented as a benefit of EADL 7,17,18,42 and as a theme in qualitative studies 22,26,28,29 . Our study highlights that safety and security is a psychological construct as well as a physical construct.…”
Section: Time Alonementioning
confidence: 99%
See 2 more Smart Citations